Penggunaan bahan-bahan minyak kelapa sawit sebagai agen pemulihan asfal terpakai - Hainin, Mohd. Rosli (Faculty of Civil Engineering, 1993)
Recycling bituminous road materials has the potential to save money, energy and scarce resources. These advantages can be realised provided the in-service performance of recycled materials (milling waste) is similar to that of comparable new material. In this report, the performance of asphaltic concrete milling waste which to be used as recycled wearing course, has been investigated and evaluated in laboratory using Wheel Tracking test. Two types of rejuvenating agent used are Palm Olein and Cyclogen. The purpose of using these rejuvenating agents is to restore the old bitumen characteristics to a consistency level appropriate for construction purposes and for durability. Apart from that palm olein is local product and its supply is surplus. Cyclogen is the currently used rejuvenating agent imported from oversea and expensive. However, it is reported that cyclogen is also a carcinogeric agent.